Oil, gold, stones: cultural value in Italian cultural policy. (7th May 2019) - Borchi, Alice
Abstract : Purpose: The purpose of this paper is to understand the concept of cultural value promoted by the Italian government between 2008 and 2018. Furthermore, it aims at setting the scope for further research and debate on the issue of cultural value in Italian cultural policy by questioning market-driven understanding of value. Design/methodology/approach: In order to do so, it examines the rhetoric of Italian policymakers, with a particular focus on the people who have covered the role of Ministry for Cultural Assets and Activities over this 10-year span, and the policies they have implemented. The various nuances of the concept of valorizzazione are studied by analysing different pathways employed by the Italian government and the values underpinning them, with a particular focus on the abandonment of heritage sites. Findings: What emerges from this research is the centrality of the economic value of culture; however, the economic impact of Italian cultural assets is always presented as a potential that has to be unlocked by implementing policies of valorizzazione, a term that has a double meaning of promotion and exploitation (Belfiore, 2006 ). Originality/value: This paper presents an original approach to understanding the formation and promotion of cultural value at the level of governmental policy in the context of contemporary cultural policy in Italy. In particular, it evidences how the centrality of the economic value of culture has remained unscathed despite the rapid change of governments that has characterised Italian politics in the last 10 years.